SPECIAL ASPECTS OF MOTOR FITNESS INFLUENCE ON LEVEL OF 11-13 YEARS’ AGE GIRLS’ PHYSICAL EXERCISES’ MASTERING - O.V. Ivashchenko (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2017)
Purpose: to find special aspects of motor fitness influence on level of 11-13 years’ age girls’ physical exercises’ mastering. Material: in the research 11 years’ age girls (n=51), 12 years’ age (n=54) and 13 years (n=63) participated. Results: By physical condition indicators all girls statistically confidently differ. We registered increase of body height indicators (by 12%), body mass (13%), vital capacity of lungs (by 12.8%), right hand strength (by 15%) and left hand strength (by 13.8%). In girls of 11-13 years’ age we registered positive dynamic of physical condition, motor abilities and level of gymnastic exercises’ mastering indicators. It was found that in total dispersion results’ variation by 81.259%, 79.353%, 71,019% are determined by such factors: physical condition, motor abilities, level of physical exercises’ mastering. In factorial structure level of physical exercises’ mastering has weight 16.435% (11years), 27.963% (12 years) and 17.010% (13 years). Conclusions: Analysis showed that in 11-13 years age girls motor abilities’ training level is effective if it becomes a component of mastered motor skills.